Features of the Blood Supply of Cardiac Myxoma which Can Cause Bleeding - Rostyslav M. Vitovskyi; Volodymyr V. Isaienko; Oleksandr A. Pishchurin; Andrii R. Vitovskyi; Maryna M. Serdiuk; Valentina P. Zakharova (Ukrainian Journal of Cardiovascular Surgery, 2022)
With a mortality rate of 1 % to 5 %, surgical treatment of cardiac myxomas (CM) may be complicated by the development of intra- or postoperative bleeding, among other things.The aim. To present an unusual case of surgical treatment of left atrial myxoma with the occurrence of intraoperative bleeding, which was due to extremely rare features of the coronary circulation with a special blood supply to the base of the CM.Case report. Female patient R., 65 years old, case record No.3686, was admitted to the National Amosov Institute of Cardiovascular Surgery of the National Academy of Medical Sciences of Ukraine with diagnosis of CM. Coronary angiography revealed unique features of coronary circulation: an arteriovenous malformation from the distal parts of the circumflex branch of the left coronary artery with discharge into the right parts of the heart was revealed. On 9/20/2022, urgent operation of resection of the myxoma of the left atrium (LA) was performed. After removal of the myxoma and sealing of the heart, accumulation of arterial blood was found in the area of the inferior vena cava (IVC) and the interatrialsulcus. Revision of the left atrium cavity was performed again:all intracardiac sutures in the area of the myxoma base were duplicated. After repeated resealing of the heart chambers, bleeding from the IVC region stopped after administration of protamine sulfate and tight tamponade of the space under the IVC. Tampons were removed from the pericardial cavity after 72 hours.Results. The source of the bleeding could be the site of the malformation of the coronary arteries, which is a tangle of small vessels located in the projection of the base of the myxoma below the point where the IVC meets the right atrium. During the histological examination of the myxoma, large full-blood vessels of the sinusoidal type were revealed, around which, due to damage to their thin walls, hematomas formed, giving the tumor a spotted appearance. The peculiarity of this tumor was the presence of a very large vascular plexus at its base; it had the appearance of a cluster of sections of numerous, different-sized, deformed and remodeled arteries. These data were confirmed by coronary angiography.Conclusions. Studying the data of coronary angiography with the analysis offeatures of localization of coronary arteries, as well as the presence of possible coronary malformations, can provide information that allows predicting the possibility of their damage, especially in the case of localization in the place of possible surgical manipulation. In the event of bleeding, one of the optimal methods of its elimination is the use of long-term tamponade.